A carrageenan-based edible coating incorporating with peppermint essential oils to increase shelf life of bananas (Musa acuminata cavendish) - Amin Pamungkas; Zaenal Arifin Siregar; Bakti Berlyanto Sedayu; Ahmat Fauzi; Toni Dwi Novianto (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2023)
Ambon bananas (Musa acuminata cavendish) are nutritious and economically valuable fruits. Bananas, being a climacteric fruit, have the potential to undergo deterioration subsequent to the harvesting process. The utilization of an edible coating on bananas has demonstrated potential in delaying spoilage, whereas the substantial use of peppermint oil has been observed in the preservation of fruit freshness. This research investigated how a carrageenan-based coating and peppermint essential oil enhance banana shelf life. This research compares uncoated bananas, carrageenan-coated bananas, and carrageenan-peppermint-coated bananas. Weight loss, total soluble solids (TSS), pH, colour, and water activity were tested. In this study, it was observed that the application of a carrageenan edible coating resulted in a reduction in weight loss and TSS as compared to bananas that were not coated. Duncan's test shows statistically significant discrepancy in weight loss among bananas that have undergone different treatments, thereby influencing the overall weight loss outcome. There are variations in pH levels and aw values. Meanwhile, pH and water activity of coated and uncoated bananas were relatively the same and stable during storage, so the carrageenan edible coating treatment and the addition of peppermint essential oil had no effect. The findings indicate that edible coatings made from carrageenan have the ability to inhibit the ripening process of bananas. Nevertheless, the efficacy of this inhibition decreases when peppermint essential oil is given as a supplementary constituent.